Relationship between death anxiety and health-related quality of life among diabetic patients: The predictive roles of experiential avoidance - Emmanuel Sochukwuma Ezaka; Reyam Nehad Nassif; Okoli Paul Chibuike; Suhanya Okeke; Okpara Titus Chukwubuzo; Chime Peter Ekpunobi; Ozougwu Augustine Obumneme; Okoli Alexander Chinwike (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2022)
This study investigated the predictive roles of experiential avoidance on the relationship between death anxiety and health-related quality of life among diabetic patients. A total of one hundred and five (105) participants (62; 58.5% females) participated in the study. The participant ages ranged from 21-75 years with a mean age of 53.45 and a standard deviation of 14.44. Participants were drawn using the convenience sampling technique and were administered the questionnaires before their consultations. Three instruments were used in data collation namely; the Death Anxiety Inventory-Revised (DAI-R), the Acceptance and Action Questionnaire (AAQ), and the Diabetes Quality of Life Questionnaire (DQOLQ). Four hypotheses were tested and the results showed that there was no significant correlation between death anxiety and HRQoL (r=-.036), also, experiential avoidance didn't significantly predict HRQoL (.411, p<.05), experiential avoidance didn't significantly predict death anxiety (.534, p<.05), while experiential avoidance didn't predict the relationship between death anxiety and HRQoL (.757, p<.05). The researchers suggest that medical professionals in charge of diabetic patients should look beyond HRQoL and death anxiety in investigating whether there will be an occurrence of experiential avoidance.